2009
DOI: 10.2529/piers081001110156
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Sensor Networks in Agriculture: Cattle Monitoring for Farming Industries

Abstract: This paper investigates an adaptation of Wireless Sensor Networks (WSNs) to cattle monitoring application. The proposed solution facilitates a desired requirement of continuously assessing the condition of individual animal, aggregating and reporting these data to the farm manager. There are several existing approaches to animal monitoring, from using a store and forward mechanisms to employing a GSM technique. These approaches for monitoring livestock health can only provide sporadic information and introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Also, it is expected that in the future, objective methods of temperament assessment will be applied in practice using the latest technical solutions (Huhtala et al, 2007;Kwong et al, 2009). For example, König et al (2006) suggested that frequency of voluntary entry of dairy cows into an automatic milking system could be used to estimate breeding value for animal temperament.…”
Section: Objectivity Of Methods For the Assessment Of Cattle Behaviourmentioning
confidence: 99%
“…Also, it is expected that in the future, objective methods of temperament assessment will be applied in practice using the latest technical solutions (Huhtala et al, 2007;Kwong et al, 2009). For example, König et al (2006) suggested that frequency of voluntary entry of dairy cows into an automatic milking system could be used to estimate breeding value for animal temperament.…”
Section: Objectivity Of Methods For the Assessment Of Cattle Behaviourmentioning
confidence: 99%
“…Other than that, the old style "Bunk Feeders" [8][9][10] have numerous limitations such as over consumption, waste, and exposure to the elements as well as wildlife consumption. Although, the solution for monitoring and control the cattle farm operation and environmental condition available [11][12][13][14][15][16] but the existing are still lacking of an automated feeder system. An effient feeding system can produce cattle that are physical and geneticly healthy [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large number of works to develop automated systems for tracking or monitoring livestock using wireless sensor network technology [3], [5][6][7][8]. However, there are some problems in using the existing wireless sensor network-based systems for tracking livestock movements in the Mongolian nomadic herding which is characterized by a large number of livestock and vast pastureland.…”
Section: Introductionmentioning
confidence: 99%